Gender Dynamics and Justice in Tribal Communities of Himachal Pradesh - Sapna Devi (International Journal of Applied and Scientific Research, 2024)
This study examines gender justice within the tribal communities of Himachal Pradesh, India. Tribal societies in this region have unique cultural practices and social structures that deeply influence gender roles and expectations. The purpose of this research is to investigate the impact of these traditional frameworks on gender justice and to identify challenges and opportunities for achieving gender equality in these communities. The research uses a mixed-methods approach, combining qualitative interviews with community members, including women and local leaders, with quantitative surveys to collect comprehensive data. Fieldwork was conducted in several tribal areas of Himachal Pradesh, ensuring a broad representation of different tribal groups and perspectives. The results reveal that while traditional practices often perpetuate gender inequality, such as restricted access to education and healthcare for women, there are also positive trends towards empowerment and change. Women's involvement in local governance and community decision-making is slowly increasing, driven by both internal advocacy and support from governmental and non-governmental organizations. In conclusion, despite significant progress towards gender justice in tribal communities Himachal Pradesh, substantial barriers remain. Efforts to promote gender equality must be sensitive to the unique cultural contexts of these communities to be successful.